2019
DOI: 10.12659/msm.913542
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Protects Against Cognitive Impairment of Subthreshold Convulsant Discharge Model Rats by Activating Protein Kinase C (PKC)-Growth-Associated Protein 43 (GAP-43)-Calmodulin-Dependent Protein Kinase (CaMK) Signal Transduction Pathway

Abstract: Background Subclinical epileptiform discharges (SEDs) are defined as epileptiform electroencephalographic (EEG) discharges without clinical signs of seizure in patients. The subthreshold convulsant discharge (SCD) is a frequently used model for SEDs. This study aimed to investigate the effect of levetiracetam (LEV), an anti-convulsant drug, on cognitive impairment of SCD model rats and to assess the associated mechanisms. Material/Methods A SCD rat model was established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Several investigations into understanding the mechanism of potential therapies have identified GAP-43 as either upregulated or essential for its ameliorative effects. Levetiracetam for treatment of retinopathy ( Mohammad et al, 2019 ) as well as for the repair of convulsant- induced cognitive impairment ( Wang et al, 2019a ) directly signals through the PKC/GAP-43 signaling pathway. Similarly, TGN-020 for treatment of spinal cord injury ( Li et al, 2019b ), and senegenin for the potential treatment for Aβ-induced neurotoxicity ( Jesky and Chen, 2016 ), involve upregulation of GAP-43 protein levels for both neuroprotection and in vitro regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations into understanding the mechanism of potential therapies have identified GAP-43 as either upregulated or essential for its ameliorative effects. Levetiracetam for treatment of retinopathy ( Mohammad et al, 2019 ) as well as for the repair of convulsant- induced cognitive impairment ( Wang et al, 2019a ) directly signals through the PKC/GAP-43 signaling pathway. Similarly, TGN-020 for treatment of spinal cord injury ( Li et al, 2019b ), and senegenin for the potential treatment for Aβ-induced neurotoxicity ( Jesky and Chen, 2016 ), involve upregulation of GAP-43 protein levels for both neuroprotection and in vitro regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Wang et al also showed similar results. By injection of Raleigh Alvin (rolipram), which is an inhibitor for phosphoric acid lipase 2–4 (PDE4) that can prevent the hydrolysis of cAMP, the researchers found the increased level of cAMP and phosphorylated CREB, and reduce of immobile time of the mice ( Wang et al, 2019 ). Notably, the cAMP and MAPK signaling partially share the same proteins in depression development.…”
Section: Signaling Pathways Of Depressionmentioning
confidence: 99%
“…[5][6][7] GAP-43, which is also known as neuromodulin, F1, and B-50, is a cytoplasmic protein specific to nerve tissue and one of the principal members of the protein kinase C (PKC) family. 8,9 The GAP-43 gene contains three exons. The first exon encodes the membrane-targeting domain, the second exon encodes a calmodulin-binding domain and a PKC phosphorylation site, and the 5 0 -flanking sequence directs initiation of RNA transcription from several sites.…”
Section: Introductionmentioning
confidence: 99%